Personal Safety Apps for Rape - Yusof, Ain Sabrina (IRC, 2020)
Rape is a social evil that has reached explosive proportions. It has ruined many lives and continues to do so at a frenetic pace. No one is immune, and age us no bar. Globally, it has been revealed in statistic that at least one in every five women have experience rape or attempted rape during her lifetime. Adolescent have high rates of rape victimization than other age group. Rape myths among health care providers may have negative influence on proper care of the victims. Rape is also one of the least-reported crime of all violent crimes, studies shows that only four out of 10 rape cases have actually been reported to the police department. Rape cases that have not been reported are due to insufficiency of evidence. In order to overcome such problems faced by women the Personal Safety mobile based application is not only necessary to use but also plays a pivotal role with android software. Mobile is a small, specially designed software program, it is easy to be download and installed onto mobile devices. The use of apps has been universalized by the Apple App Store and also by Google Play Store. It can be said that an application that tackle issue about rape will improve the life of all citizens by offering them a higher degree of security in our society. The purpose of this paper is to educate and reduce the amount of sexual assault and harassment in society in order to make women feel secure in the society that they are living in.